Obtenção de filtros de celulose para aerossóis a partir de diferentes processos - Toniazzo, Rean (2022)
Given the crisis due to the SARS-CoV-2 virus pandemic and the high demand for personal protective equipment (PPE), this master's project aimed to develop a process for manufacturing biodegradable filters from a renewable source for facemasks. The proposed material is cellulose nanofiber (CNF). To achieve this, the routes explored were: drying of wood cellulose and bacterial cellulose in the presence or not of a blowing agent. The first route consisted on the drying of the membranes of pure wood and bacterial cellulose nanofibers under different conditions of temperature and drying time, generating a water-free porous non-woven fabric. The second route consisted of adding the blowing agent Azodicarbonamide (ADC) to the cellulose membranes before drying them for the expansion of the fibrillar structure, increasing the size of the pores to favor the passage of air, without losing filtering efficiency. The filters obtained were subjected to morphological characterizations by SEM images and particle collection efficiency tests and air pressure drop to evaluate their use as aerosol filters following the NBR 13698 standard. The first route produced samples that became barriers to the passage of air, due to the quantity and nanometric dimensions of the pores present in the membrane. The second route, on the other hand, was able to produce filters successfully. Filters with collection efficiencies of up to 71% for 300 nm particles were obtained. However, most filters showed a pressure drop greater than 200 Pa/cm², above the limit set by the standard of 40 Pa/cm². In addition, the blowing agent in question generates a very large amount of solid residue that can compromise the use of these filters. Therefore, the production of cellulose filters using blowing agents is possible, but the use of ADC is not ideal.